Propagation of noise generated by single moving sources in open area - JARZĘCKI, J.; MAKAREWICZ, R. (Archives of Acoustics, 1982)
The sound level (L) of noise generated by a single moving source (e.g. vehicle) is a starting point for the determination of the resultant level of noise emitted by sets of moving sources (e.g. streams of vehicles). The aim of the investigations was to find the relations among L, the motion velocity and the distance of the observation point from the source for different weather conditions. The investigations were performed in a flat area covered with concrete and grass, taking into consideration two basic vehicle types light and heavy. Logarithmic-and-linear relations between these quantities have been obtained.